(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2020)
The Presence of Podcasts is such an interesting technology to facilitate language learner development. The online or offline accessibility through a smartphone or laptop offer convenience, learning anytime and everywhere. The Audios and videos enable students for their learning accelerations .This study aimed to study the influence of podcasts as technology for Students’ English Vocabulary mastery, and to investigate the students’ responses towards podcasts. This research employed quantitative research with a quasi-experimental design. The Participants were 60 Students of SMA Negeri 2 Buru grade XII IIS, Namlea, Buru , Maluku Province. Data related to student’s vocabulary mastery were collected by implementing pre-test, post-test, and distributing questionnaires to find out students’ responses towards the use of Podcast Technology. Pre-test and post-test were conducted for .The 60 participants were then classified into 30 Students of Experimental Group. Moreover, 30 Students of Control Group .The data collected were then analyzed using IBM SPSS. The mean score resulted from the experimental group were 52.83 in the pretest and reached 63.83 in the Post Test, while the mean score resulted from Control Group were 50.5 in the Pre-Test and 55.33 in Post Test. The results indicated that the vocabulary mastery of the students in both groups was developed, however the experimental group, which implemented podcast, showed the higher improvement than non-podcast. The difference score between both groups was 8.5. The students also showed the positive responses toward the utility of podcast in teaching and learning processes.